Prevention of Minor Crimes: How Does the Sabhara Unit Maintain Public Order? - Aurora Pangastiti (Advances in Police Science Research Journal, 2021)
This research analyzes the implementation of Sabhara unit patrols in the prevention of minor crimes at the Sukabumi City Police. In this study, minor offenses were specifically related to alcoholic drinking offenses. The consumption of alcoholic drinks in the area of ​​the Sukabumi City Police must be 0%, where the reality on the ground is that people still consume alcoholic drinks. The purpose of this study was to describe the implementation of the Sabhara unit patrol and to identify the factors affecting the implementation of the patrol in preventing minor crimes. This research uses qualitative methods with data collection techniques in the form of interviews, observation and document/literature study. The interviews used were semi-structured interviews and participatory observation. The research was carried out in the Sukabumi City Police Station area. Patrol of the Sabhara Unit of the Sukabumi City Police is in accordance with the SOP in the decision of the Sukabumi City Police Chief. The patrol is divided into two, namely the preparation stage and the implementation stage. Several factors hindered the implementation of patrols, namely (1) lack of members of the existing Sabhara units, (2) lack of awareness of members in keeping secrets, (3) lack of budget for fuel oil, (4) limited patrol vehicles. Meanwhile, the factors that support the implementation of patrols are (1) division of tasks, (2) reports from the public, (3) positive community responses, (4) good welfare of patrol members. In connection with the research results, the suggestions are to make better planning, foster a sense of loyalty, add personnel, add motorized vehicles, and build good relationships with the community.